Determinants of the Effectiveness of the Islamic Insurance Industry Spin-Off Implementation in Indonesia with the Analytical Hierarchy Process Approach - Erny Arianty; Akhmad Khabibi (Journal of Islamic Economics Lariba, 2022)
This study aims to analyze the factors that have the highest level of importance in realizing the spin-off implementation of the Sharia Insurance Industry. The method used is qualitative with an Analytical Hierarchy Process (AHP) approach. Data were obtained from FGDs and AHP questionnaires with informants from AASI, the sharia life and general insurance industry, the Sharia Supervisory Board, the government, and regulators. The research results show that the clarity of policy, or spin-off criteria, has the highest importance. The sub-criteria with the highest level of importance is the clarity in value of tabarru funds which is 50% of the parent fund. The next factor is the actual practice in the industry and the function of monitoring and supervision, respectively. The factors that have the highest level of importance in realizing spin-off effectiveness are the relaxation of a specific aspect and the action of the industry, whether to continue or postpone the spin-off. These aspects include the implementation of tax relief based on the book value of the company's assets, relaxation in reducing costs that occur during and after the spin-off until the SBU is stable and independent, policies related to bank assurance, and policies related to capital. The research implication for industry and regulation considers determining integrated and coordinated efforts to achieve an effective spin-off implementation. The limitation of this research is in determining the factors not based on sub-criteria but the factors as a whole. The novelty of this research is in determining the topic and method, namely analyzing the most dominant factors to realize effectiveness with the AHP method.